Utility of triple tumor markers CA19-9, CA125 and CEA in predicting advanced stage of carcinoma gallbladder: a retrospective study - Kumar, Navin; Rajput, Deepak; Gupta, Amit; Popuri, Varun; Kundal, Ashikesh; Sharma, Jyoti; Puliyath, Nisanth; Shasheendran, Sruthi (International Surgery Journal, 2020)
Background: A combination of serum tumor markers are used in the evaluation and prognosis of carcinoma gallbladder (GBC). Aim of the study was to find the significance of combined use of CA19-9, CA125 and CEA in advanced stage of GBC and to find the cut-off value of each of these tumor markers in metastatic GBC. Methods: This was a retrospective observational cohort study over 1 year, which was carried out in 42 cases of advanced GBC. The patients were grouped in to locally advanced and metastatic stage on the basis of CECT scan findings. CA19-9, CA125 and CEA were assayed in all patients. These tumor markers were analysed with these two groups of GBCs. Statistical analysis was performed using R statistical software v3.6.2. Results: Out of 42 cases CA19-9 was elevated in 18 (78%), CA125 in 16 (70%) and CEA in 9 (39%) patients with metastatic disease. The cut-off value of CA19-9, CA125 and CEA was determined by ROC curve were >109 U/ml, 55.4 U/ml and 2.56 μg/l respectively. CA19-9 had the highest sensitivity 78.3% followed by CA125 69.6% and CEA has the highest specificity 68.4% for the diagnosis of metastatic stage of the disease. Specificity of these tumor markers were highest when used in combination. Conclusions: Combined use of triple tumor markers increases its specificity in the diagnosis of advanced stage of GBC but their cut-off level is statistically not significant in predicting metastatic GBC.